1996
DOI: 10.1093/jnci/88.13.890
|View full text |Cite
|
Sign up to set email alerts
|

Larynx Preservation in Pyriform Sinus Cancer: Preliminary Results of a European Organization for Research and Treatment of Cancer Phase III Trial

Abstract: Larynx preservation without jeopardizing survival appears feasible in patients with cancer of the hypopharynx. On the basis of these observations, the EORTC has now accepted the use of induction chemotherapy followed by radiation as the new standard treatment in its future phase III larynx preservation trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
758
1
26

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,224 publications
(818 citation statements)
references
References 11 publications
23
758
1
26
Order By: Relevance
“…Randomized Phase III data have confirmed that induction platinum-based, multiagent chemotherapy given before radiotherapy alone can provide outcomes equivalent to larynx-sacrificing surgery for locally advanced hypopharyngeal and laryngeal disease. 16,17 Until recently, induction chemotherapy before local therapy for other head and neck subsites remained out of favor due to the lack of consistent supportive Phase III evidence for a significant survival benefit. 18 -20 More current Phase III data from Europe using cisplatin and 5-FU suggest a survival benefit to induction therapy, 21 and recent Phase II results for taxanebased induction chemotherapy have further raised interest in this approach.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized Phase III data have confirmed that induction platinum-based, multiagent chemotherapy given before radiotherapy alone can provide outcomes equivalent to larynx-sacrificing surgery for locally advanced hypopharyngeal and laryngeal disease. 16,17 Until recently, induction chemotherapy before local therapy for other head and neck subsites remained out of favor due to the lack of consistent supportive Phase III evidence for a significant survival benefit. 18 -20 More current Phase III data from Europe using cisplatin and 5-FU suggest a survival benefit to induction therapy, 21 and recent Phase II results for taxanebased induction chemotherapy have further raised interest in this approach.…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike advanced laryngeal cancers, the question of organ preservation [16,20] has not been subjected to rigorous evaluation in hypopharyngeal cancers, precluding firm conclusions. The most widely discussed organ preservation trial for hypopharyngeal cancers, the European Organization for Research and Treatment of Cancer (EORTC) 24891 [21] randomized patients with advanced cancers of the hypopharynx and lateral epilarynx to induction chemotherapy followed by radiotherapy (surgery for non-responders) or surgery followed by post-operative adjuvant radiotherapy. The trial however closed prematurely after accruing 202 patients due to difficulty in getting consent for surgery.…”
Section: Organ Preservation and Hypopharyngeal Cancersmentioning
confidence: 99%
“…In contrast, the role of induction chemotherapy is not yet clear. Although not the standard of care, induction chemotherapy is used in clinical practice and is thought to be beneficial for reducing the rate of distant metastases (Paccagnella et al, 1994;Lefebvre et al, 1996), increasing organ preservation (Group, 1991;Lefebvre et al, 1996) and survival rates (Paccagnella et al, 1994;Zorat et al, 2004). Combining induction and concomitant chemotherapy with radiation, that is, in a sequential treatment approach, has the potential for improving disease outcomes.…”
mentioning
confidence: 99%